2017
DOI: 10.21077/ijf.2017.64.2.60341-07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermentation methods on amino acids, fiber fractions and anti nutritional factors in different plant protein sources and essential amino acid index for Penaeus (Litopenaeus) vannamei

Abstract: The incorporation of plant protein sources in shrimp feed is limited due to unbalanced amino acids and higher anti-nutrients. In the present study, soybean meal (SBM), groundnut oil cake (GNC), rapeseed meal (RSM), sunflower oil cake (SFC) and guar meal (GRM) were subjected to natural, bacterial, fungal and yeast fermentation methods. The essential amino acid contents were increased by 4-28% in SBM, 7-26% in GNC, 3-27% in RSM, 8-18% in SFC and 4-14% in GRM. The increase was better for lysine with fungal fermen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 18 publications
(28 reference statements)
5
51
0
5
Order By: Relevance
“…Solid state fermentation is embraced as an economically viable processing technique in recent years, which in part or totally defeats the limitations related with plant protein sources (Shi et al, ). The effect of microbial fermentation using bacteria (Imelda et al, ), fungus (Jannathulla, Dayal, Vasanthakumar, Ambasankar, & Muralidhar, ; Shi et al, ) and yeast (Sharawy, Goda, & Hassaan, ) on fishmeal substitution have been reported earlier. Though various microorganisms are being used for solid state fermentation, the filamentous fungus is an important group among them.…”
Section: Approaches For Utilization Of Plant Protein Sourcesmentioning
confidence: 81%
“…Solid state fermentation is embraced as an economically viable processing technique in recent years, which in part or totally defeats the limitations related with plant protein sources (Shi et al, ). The effect of microbial fermentation using bacteria (Imelda et al, ), fungus (Jannathulla, Dayal, Vasanthakumar, Ambasankar, & Muralidhar, ; Shi et al, ) and yeast (Sharawy, Goda, & Hassaan, ) on fishmeal substitution have been reported earlier. Though various microorganisms are being used for solid state fermentation, the filamentous fungus is an important group among them.…”
Section: Approaches For Utilization Of Plant Protein Sourcesmentioning
confidence: 81%
“…Besides the knowledge on ADMD and APD, the plant protein sources could effectively be used in feed formulation when their AAD values are known. The result of our earlier study (Jannathulla et al, 2017;Jannathulla, Dayal, Vasanthakumar et al, 2018) showed an enhanced digestibility of fungal fermented ingredients compared to their respective untreated ones in P. vannamei. In the present investigation, the average of total essential AAD was high in FSBM and was >90% for both the species, whereas the FRSM and FSFC had the lowest average in P.monodon and P. indicus respectively.…”
Section: Discussionmentioning
confidence: 77%
“…In this case, fermented plant proteins have been explored as potential protein sources in the diet of shrimp due to their improved nutritional quality compared to their respective untreated ones. In our earlier study (Jannathulla, Dayal, Vasanthakumar, Ambasankar, & Muralidhar, ), it was found that the microbial fermentation had significantly reduced fibre fractions and anti‐nutrients, while the essential amino acids, especially methionine, lysine, and tryptophan were found to be increased. Though the fermented materials have been used with varying degree of success in the diet of shrimp, replacing fishmeal completely by using these ingredients is a quite challenging task for the researchers, which indicates the poor availability of nutrients from the ingredients even after fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Kalanjiam () reported that Penaeus monodon fed a diet with 2.5% of GRM treated with enzymes resulted in significantly ( p < .05) reduced growth performance than those fed a diet containing no GRM. In our earlier study (Jannathulla, Dayal, Vasanthakumar, Ambasankar, & Muralidhar, ), it was observed that GRM could not be included beyond 2.5% in the diet of Penaeus vannamei even after fermentation. Hence, the present investigation was carried out to comprehend the availability of nutrients, in particular amino acids from both untreated and fungal ( Aspergillus niger ) fermented GRM in two different penaeid shrimp species viz., Penaeus indicus and P. monodon .…”
Section: Ingredient Composition Of Reference Diet Used For In Vivo DImentioning
confidence: 92%
“…Guar meal (GRM) was fermented using a GRAS (Generally Recognized As Safe-RAS Notice No: 35, 2010) listed fungus, A. niger (Jannathulla et al, 2017b(Jannathulla et al, , 2017cJannathulla, Syama Dayal, Ambasankar, & Muralidhar, 2017a). The reference diet (Table 1) and both the test diets were formulated according to the method of Dayal, Rajaram, Ambasankar, and Ali (2011).…”
mentioning
confidence: 99%